The Influence Of Asset Management On Optimization Of The Use Of Fixed Assets In The Government Sector : Literature Review - Fauziah, Nur Israq; Mediawati, Elis (IJBLE Scientific Publications Community Inc., 2024)
To implement asset management, there are four steps that must be taken so that assets can be utilized optimally. The four steps include asset inventory, legal audit, asset assessment, and asset monitoring and control. First, asset inventory. Of the 25 articles, 24 articles stated that there was an influence, and 1 article stated that there was no influence. Second, in the legal audit, there were 18 articles that stated there was an influence, and 7 articles stated that there was no influence. Third, in asset assessment, 19 articles stated that it had an effect and 3 articles stated that it had no effect. Fourth, monitoring and controlling assets, there are 13 journals, 12 articles stating they have an influence and 1 article stating they have no influence. The research method in this research is a literature review. It is hoped that the benefits of this research can be used as a reference for further research.